Pathophysiology and Management of Parkinsonian Tremor - Helmich, Rick C.; Dirkx, Michiel F. (Seminars in Neurology, 2017)
Parkinson's tremor is one of the cardinal motor symptoms of Parkinson's disease. The pathophysiology of Parkinson's tremor is different from that of other motor symptoms such as bradykinesia and rigidity. In this review, the authors discuss evidence suggesting that tremor is a network disorder that arises from distinct pathophysiological changes in the basal ganglia and in the cerebellothalamocortical circuit. They also discuss how interventions in this circuitry, for example, deep brain surgery and noninvasive brain stimulation, can modulate or even treat tremor. Future research may focus on understanding sources for the large variability between patients in terms of treatment response, on understanding the contextual factors that modulate tremor (stress, voluntary movements), and on focused interventions in the tremor circuitry.
Keywords: Parkinson's disease; tremor; basal ganglia; treatment